2017
DOI: 10.1557/adv.2017.519
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Copper, Nickel and Ternary Alloys Cu-Ni-Zr Obtained by Mechanical Alloying and Hot Pressing

Abstract: Elemental powders of Cu and Ni, binary alloys (Cu-Ni and Cu-Zr) and ternary alloy (Cu-Ni-Zr) obtained by mechanical alloying and uniaxial compaction hot microstructure and mechanical properties were investigated. The alloys studied were: pure Cu, pure Ni, binary alloys (Cu-Ni; Cu-Zr) and ternary alloys (Cu-Ni-Zr) under the same mechanical milling and hot pressing conditions. The samples were analyzed by X-ray diffraction (XRD), scanning electron microscope (SEM); the mechanical properties were studied by compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The experimental density and relative density values of Cu–Al alloys are given in Table 2. Various studies on Cu-based alloys revealed that the relative density of hot-pressed alloys of Cu reportedly varied between 72 and 90.7% depending on the processing conditions and composition [2729]. From this, it can be realised that the selected hot-pressing parameters (500°C, 500 MPa and 30 min.)…”
Section: Resultsmentioning
confidence: 99%
“…The experimental density and relative density values of Cu–Al alloys are given in Table 2. Various studies on Cu-based alloys revealed that the relative density of hot-pressed alloys of Cu reportedly varied between 72 and 90.7% depending on the processing conditions and composition [2729]. From this, it can be realised that the selected hot-pressing parameters (500°C, 500 MPa and 30 min.)…”
Section: Resultsmentioning
confidence: 99%